2022
DOI: 10.1097/ico.0000000000003202
|View full text |Cite
|
Sign up to set email alerts
|

Sutured Descemet Membrane Endothelial Keratoplasty in Patients With Complex Anatomy or Difficulty Positioning

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It should be noted that 1 group of investigators also reported a series of 3 DMEK grafts in which full-thickness sutures were placed tangential to the graft edge. 20 The American Academy of Ophthalmology's Technology Assessment of DSEK reported graft detachment as the most common complication in a review of literature before 2011. 2 The average detachment rate among studies was 14.5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that 1 group of investigators also reported a series of 3 DMEK grafts in which full-thickness sutures were placed tangential to the graft edge. 20 The American Academy of Ophthalmology's Technology Assessment of DSEK reported graft detachment as the most common complication in a review of literature before 2011. 2 The average detachment rate among studies was 14.5%.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that 1 group of investigators also reported a series of 3 DMEK grafts in which full-thickness sutures were placed tangential to the graft edge. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both canines and humans, graft detachment is a potential complication with DSEK. In this case, nonabsorbable 10-0 Ethilon sutures were applied dorsally and ventrally to anchor the graft to the adjacent recipient stroma, a technique we have described in humans [ 8 ]. However, placement of sutures could lead to other possible complications such as epithelial cell downgrowth or focal fungal or bacterial infection, and sutures should be monitored and/or removed postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…This bubble is expected to dissolve in about two days but provides structural support until it disappears. 10-0 nylon sutures were used to fix the graft in place using a technique we have reported for human EK [ 8 ]. Subconjunctival injections of betamethasone and gentamicin were administered.…”
Section: Case Presentationmentioning
confidence: 99%